Preliminary Investigation of Antimicrobial Property of Acacia leucophloea Leaves Extract - Rajesh Gupta,; Arun K Gupta,; Rajeev K Singla,; G Aiswarya, (International Journal of Phytomedicine, 2011)
Leaves of indigenous plant Acacia leucophloea have been successively extracted using different solvents like hexane, methanol and water. Extract was evaluated for its antibacterial activity using two assay method Kirby bauer disc diffusion and tube dilution assay. Results of the given study revealed that the methanolic extract is potential antibacterial agent specifically for E coli & & S aureus.